Small world phenomena and performances of wireless ad hoc networks - Trajanov, Dimitar; Filiposka, Sonja; Grnarov, Aksenti (My University, 2004)
The groups of people that use an ad hoc network form a social network that exhibits small world properties. In this paper the impact of small world phenomena in application layer network on performance of ad hoc network is investigated. We show that small world properties have a big influence on the performance taking into consideration different routing protocols and network area shapes. In order to quantify the influence of small world properties on ad hoc network performances, two parameters are used: clustering coefficient and average hop distance. The average hop distance is a measurement for overlapping of logical and physical network. We also propose a new algorithm for generation of small world networks.
Keywords: ad hoc network, small world, performance, application layer